Kinerja Perusahaan Daerah Air Minum Madiun Umbul Square di Kabupaten Madiun Berdasarkan Metode Balanced Scorecard - Marfuah, Evie Titin Marfuah Titin Marfuah; S, Sutomo; A, Anwar (e-Sospol, 2017)
Abstract This aimed to describe the performance of PD. Madiun Umbul Square in 2014 using Balanced Scorecard method. The problem in this research covers financial problems in the form of the decline in the company earnings and nonfinancial problems faced by service management. Municipal companies that have a goal in financial and nonfinancial matter need performance measuring tools to measure the performance aspect of those goals. The research used descriptive type with quantitative approach. The research was focused on the measurement of four variables in Balanced Scorecard i.e. financial perspective, pelanggan perspective, internal business perspective, and learning and growth perspective translated in the performance indicators. The location of research was at PD. Madiun Umbul Square. Informants were selected using purposive and snowball sampling, and the respondents were all employees of PD. Madiun Umbul Square. Data were collected using questionnaire, unstructured interview and documentation. Validity and reliability of data were examined by using product moment correlation and internal consistency. Data were analyzed using descriptive statistical analysis by analyzing the data obtained from the four performance variables in balanced scorecard and described without generalization. The results showed that the performance of PD. Madiun Umbul Square from financial perspective variable was 21.78% with very good performance criteria, from pelanggan perspective variable was 27% with very good performance criteria, from internal business perspective variable was 19.51% with good performance criteria, and from learning and growth perspective variable was 20.21% with good performance criteria. It was concluded that the performance of PD. Madiun Umbul Square in 2014 was in good criteria but had experienced a decrease in performance compared to that in 2013; only pelanggan perspective variable met performance target.